2020
DOI: 10.1038/s41598-020-75807-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metallothionein-knockdown on cisplatin resistance in malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare, but aggressive tumor with dismal prognosis. Platinum-based chemotherapy is regularly used as part of multimodality therapy. The expression of metallothioneins (MT) has been identified as a reason for cisplatin resistance, which often leads to early therapy failure or relapse. Thus, knockdown of MT expression may improve response to cisplatin treatment. The MT gene- and protein expression of the MPM-cell lines MSTO-211H, NCI-H2052 and NCI-H2452 and the human fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…CYP3A4 overexpression in lung and primary breast cancers has been documented to contribute to docetaxel resistance [ 67 , 68 ]. Cisplatin can be inactivated by the overexpression of metallothioneins (MTs), leading to cisplatin resistance in cancers [ 69 , 70 ].…”
Section: Drug Resistance In Cancer and Its Mechanismsmentioning
confidence: 99%
“…CYP3A4 overexpression in lung and primary breast cancers has been documented to contribute to docetaxel resistance [ 67 , 68 ]. Cisplatin can be inactivated by the overexpression of metallothioneins (MTs), leading to cisplatin resistance in cancers [ 69 , 70 ].…”
Section: Drug Resistance In Cancer and Its Mechanismsmentioning
confidence: 99%
“…MT gene and protein levels increase following the exposure of different metals in both mouse and humans. Recently, it has been suggested that MT promotes chemoresistance during metal-based cancer chemotherapies ( Borchert et al., 2020 ; Rodrigo et al., 2021 ). Cisplatin is a platinum-based compound, commonly used in chemotherapy treatments alone or in combination with other drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In transurethral or ureteroscopic biopsy, specimens immunostained with MT2A can identify high-risk patients who should receive aggressive surgery to prevent undertreatment. Moreover, recent studies have demonstrated that high MT2A expression is a predictive biomarker of cisplatin resistance in osteosarcoma and mesothelioma [29,30]. Therefore, aggressive or novel therapeutic protocols should be considered and investigated in patients with UC with high MT2A expression.…”
Section: Discussionmentioning
confidence: 99%